Nihonella gen. nov., a new troglophilic genus of dwarf spiders from Japan with a discussion on its phylogenetic position within the subfamily Erigoninae (Araneae, Linyphiidae) - Ballarin, Francesco; Yamasaki, Takeshi (European Journal of Taxonomy, 2021)
A new monospecific genus belonging to the family Linyphiidae Blackwell, 1859, Nihonella gen. nov., is described using an integrative taxonomic approach based on the species N. chika gen. et sp. nov. The new genus is endemic to Western Honshu, Japan, and it shows distinctive genitalic and somatic characters of other genera of the subfamily Erigoninae Emerton, 1882. Nihonella gen. nov. is found only in the twilight and transition zones of caves in Okayama and Nara Prefectures. The phylogenetic position of Nihonella gen. nov. within the subfamily Erigoninae, and its relationship as a sister clade of the species of the group of Savignia Blackwell, 1833 (sensu Millidge 1977), is discussed on the basis of both, morphological and molecular evidence.